"Tragic girls" and "crack whores": Alcohol, femininity and Facebook. (February 2016) - Hutton, Fiona; Griffin, Christine; Lyons, Antonia; Niland, Patricia; McCreanor, Tim
New Zealand, similar to many other westernised nations, has a well-developed national culture of drinking to intoxication. Within this cultural context, young women are exhorted to engage with the night time economy, get drunk and have "fun" without relinquishing claims to "respectability". More recently, the rise of Facebook and other social networking sites has coincided with shifts in postfeminism, neo-liberalism and the development of the night time economy. Social networking sites have become a mundane part of people's everyday lives, whilst still reflecting structural constraints such as class, ethnicity and gender. This article reports on a qualitative study of young women's drinking practices and uses of Facebook. Focus group discussions were conducted with eight friendship groups involving 36 participants aged 18–25 years. Transcripts of these discussions were subjected to thematic analysis. Three key themes were identified: "tragic girls" and "crack whores"; "drunken femininities"; and "Facebook, alcohol and drunken femininities". The results indicated that young women experienced significant tensions in expressing their "drunken femininities" both in public and online, whilst also engaging in "airbrushing" of Facebook photos to minimize the appearance of intoxication for known and unknown audiences.